2022
DOI: 10.1109/tcds.2021.3094555
|View full text |Cite
|
Sign up to set email alerts
|

Vector Field Streamline Clustering Framework for Brain Fiber Tract Segmentation

Abstract: Brain fiber tracts are widely used in studying brain diseases, which may lead to a better understanding of how disease affects the brain. The segmentation of brain fiber tracts assumed enormous importance in disease analysis. In this paper, we propose a novel vector field streamline clustering framework for brain fiber tract segmentations. Brain fiber tracts are firstly expressed in a vector field and compressed using the streamline simplification algorithm. After streamline normalization and regular-polyhedro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In these studies, fibers from the whole brain are classified into anatomically meaningful fiber tracts based on labeled training datasets. To alleviate the requirement of ground truth labels, recent studies have shown the potential of using unsupervised deep learning for WMFC [41], [63]. In [63], an auto-encoder based neural network is adopted to achieve fiber clustering; however, it requires complex feature extraction procedures to generate inputs of the neural network.…”
Section: B Unsupervised Feature Learning and Clusteringmentioning
confidence: 99%
“…In these studies, fibers from the whole brain are classified into anatomically meaningful fiber tracts based on labeled training datasets. To alleviate the requirement of ground truth labels, recent studies have shown the potential of using unsupervised deep learning for WMFC [41], [63]. In [63], an auto-encoder based neural network is adopted to achieve fiber clustering; however, it requires complex feature extraction procedures to generate inputs of the neural network.…”
Section: B Unsupervised Feature Learning and Clusteringmentioning
confidence: 99%
“…Over the past few decades, various medical image segmentation algorithm have been presented, which can be broadly grouped into thresholding ( Jain and Singh, 2022 ; Rawas and El-Zaart, 2022 ), watershed ( Mohanapriya and Kalaavathi, 2019 ; Sadegh et al, 2022 ), clustering ( Xu et al, 2022 ; Zhou et al, 2022 ), conditional random field ( Sun et al, 2020 ; Li et al, 2022 ), dictionary learning ( Yang Y Y et al, 2020 ; Tang et al, 2021 ), graph cut ( Gamechi et al, 2021 ; Zhu et al, 2021 ), region growing ( Rundo et al, 2016 ; Biratu et al, 2021 ), active contour ( Dake et al, 2019 ; Shahvaran et al, 2021 ), quantum-inspired computing ( Sergioli et al, 2021 ; Amin et al, 2022 ), computational intelligence ( Vijay et al, 2016 ; Zhang et al, 2022 ). These traditional methods rely on developers to design algorithms for specific applications.…”
Section: Introductionmentioning
confidence: 99%
“…Three clustering methods, namely K-means, hierarchical clustering, and spectral clustering, were used to effectively classify the chaotic streamline, which provided a favorable reference for further visualization of the streamline (Qi, 2015). The dynamic time regularization algorithm and the mean minimum distance between adjacent points were used to measure the similarity of streamlines, simplify the flow field, and improve the visualization (Lintao); and through streamline normalization and regularpolyhedron projection, high-dimensional features of each fiber tract are computed and fed to the IDEC clustering algorithm for clustering, which also provide qualitative and quantitative evaluations of the IDEC clustering method and QB clustering method (Xu et al, 2021). A streamline numerical simulation method (Hu and Lihui, 2018) was presented, which calculates the average attribute of streamlines and then applies a clustering method to identify the flow field of the water-drive reservoir.…”
Section: Introductionmentioning
confidence: 99%